Programming Provided by Religious Congregations in the United States to Address Mental Illness and Substance Use Disorder - Holleman, Anna (Journal of religion and health, 2024)
Mental health conditions, including substance use disorders, are one of the most commonly occurring yet least commonly treated health ailments in the United States. Religious congregations serve as important providers of mental health services, as they can fill this gap with accessible care. This study provides an up-to-date accounting of mental health service provision by religious congregations, using a nationally representative survey of U.S. congregations collected in 2012 and 2018-19. Half of all congregations in the U.S. provided a program or service targeting mental illness or substance use disorder in 2018-19, and rates of provision increased among Christian congregations between 2012 and 2018-19.